2001
DOI: 10.1002/gcc.1140
|View full text |Cite
|
Sign up to set email alerts
|

Combined copy status of 18q21 genes in colorectal cancer shows frequent retention of SMAD7

Abstract: Deletions of chromosome band 18q21 appear with very high frequency in a variety of carcinomas, especially in colorectal cancer. Potent tumor suppressor genes located in this region encode transforming growth factor beta (TGF-beta) signal transducers SMAD2 and SMAD4, and inactivation of either one leads to impaired TGF-beta-mediated cell growth/apoptosis. Following the assignment of SMAD7 to 18q21, we first refined the SMAD7 gene position within this region by genetically mapping SMAD7 between SMAD2 and SMAD4. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…Because Smad7 can inhibit the anti-proliferative TGF-␤ signaling, Smad7 overexpression may be an additional mechanism by which cells progress on their path to a transformed phenotype. Consistently, overexpression of Smad7 has been noted in pancreatic and colon cancers (29,30).…”
supporting
confidence: 58%
“…Because Smad7 can inhibit the anti-proliferative TGF-␤ signaling, Smad7 overexpression may be an additional mechanism by which cells progress on their path to a transformed phenotype. Consistently, overexpression of Smad7 has been noted in pancreatic and colon cancers (29,30).…”
supporting
confidence: 58%
“…Degradation of Mdm2 can stimulate the p53 pathway (36). In addition, inhibitory Smads, feedback inhibitors of TGF-␤ signaling, are overexpressed in some types of tumors (37,38) and are degraded by ubiquitination (39). Therefore, degradation of feedback inhibitors might be a fundamental strategy in various processes that control cell signals.…”
Section: Discussionmentioning
confidence: 99%
“…SMAD2, SMAD7 and DCC data were available for 197, 178 and 206 samples, respectively. The total of 264 patients comprises 164 individuals described in our previous study 15 and 100 additional patients.…”
Section: Patientsmentioning
confidence: 99%
“…We recently reported that the deletion frequency of SMAD7, significantly lower than those of SMAD2 or SMAD4, reflects the frequent association of SMAD2 and SMAD4 gene deletion with retention of the SMAD7 gene located in between. 15 In addition, we have also defined SMAD4 as a predictive marker for benefit of chemotherapy in patients with CRC, suggesting that integrity of this component of the TGF␤/BMP signaling pathway may also be a condition for efficiency of chemotherapy. 21 We aimed to test whether the deletion of 18q21 genes SMAD2 and SMAD7, plus the DCC gene 3 located nearby, would have a significant influence on the outcome of patients with CRC.…”
mentioning
confidence: 94%
See 1 more Smart Citation